Oral health education: An overview of oral health among university students (Research, Society and Development, 2025)
Introduction: The maintenance of oral health plays a crucial role in promoting health and well-being, significantly influencing the quality of life of human beings. Objective: The purpose of this study is to investigate the oral hygiene habits of students from different courses at Parana University – UNIPAR, in Brazil. Methodology: A total of 705 participants were evaluated through a questionnaire, and the data were analyzed using tables, graphs, and measures of central tendency. Results and discussion: among the analyzed courses, Dentistry presented the best brushing indices (36%), while the Nursing course obtained the lowest adherence rate, with 20% of students reporting brushing their teeth only once a day or never. Regarding the use of dental floss, the Dentistry course had 81% of students reporting its use after every brushing, whereas the Administration course showed the lowest result, with 16% reporting never using dental floss. In relation to the use of mouthwash, 37% of Administration students reported using it daily; however, 29% of these students stated that they replaced brushing with mouthwash. The most prevalent diseases among the participants were caries (67%), aphthous ulcers (45%), and dental calculus (26%). Next were gingivitis (21%), bruxism (20%), and halitosis (19%). Approximately 31% seek dental consultations only in cases of urgency, without pursuing preventive dental follow-up. Conclusion: The most recurrent oral diseases are caries and dental calculus. The analyses reinforce the importance of institutional strategies that promote oral health education, to broaden the reach of preventive actions in the university environment.